2021
DOI: 10.1186/s12937-021-00719-z
|View full text |Cite
|
Sign up to set email alerts
|

Energy drink consumption among Australian adolescents associated with a cluster of unhealthy dietary behaviours and short sleep duration

Abstract: Background Non-alcoholic energy drinks (‘energy drinks’) are high in sugar, as well as caffeine, leading to concerns regarding their suitability for children and adolescents. Despite this, marketing of energy drinks is often directed at adolescents, and there are no age restrictions on the sale of these products in Australia. The current study aimed to examine patterns in consumption of energy drinks among Australian secondary school students and identify sociodemographic and behavioural correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 76 publications
5
17
2
3
Order By: Relevance
“…As both sleep onset and sleep offset were shifted later following caffeinated beverage consumption in the current study, there was no net effect on sleep duration. Previous studies examining the link between caffeine consumption and self-reported sleep duration in adolescents have been mixed [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 ], while two studies that measured sleep through actigraphy as in the current study found no cross-sectional association between caffeine consumption and sleep [ 21 , 22 , 23 ]. It is possible that self-reported and objectively measured sleep duration capture different constructs, and that adolescents who consume more caffeine perceive their sleep to be shorter without an actual difference in sleep duration.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…As both sleep onset and sleep offset were shifted later following caffeinated beverage consumption in the current study, there was no net effect on sleep duration. Previous studies examining the link between caffeine consumption and self-reported sleep duration in adolescents have been mixed [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 ], while two studies that measured sleep through actigraphy as in the current study found no cross-sectional association between caffeine consumption and sleep [ 21 , 22 , 23 ]. It is possible that self-reported and objectively measured sleep duration capture different constructs, and that adolescents who consume more caffeine perceive their sleep to be shorter without an actual difference in sleep duration.…”
Section: Discussioncontrasting
confidence: 67%
“…Specifically, for every extra SD -hour of variability in sleep duration and midpoint, adolescents were 17% and 21% more likely to consume at least one caffeinated beverage on average across monitoring days. We also measured sleep through objective measures, unlike previous studies that measured sleep through self-report [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 39 ]. Variable sleep schedules may contribute to daytime sleepiness due to circadian misalignment [ 60 ], which could lead to increased caffeinated beverage consumption to maintain alertness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transition to university in young adults involves a greater autonomy concerning food choices, low food budget, and exposure to new social groups than usual [ 5 , 6 ]. Indeed, the transition from living at home with parents to autonomous university life is often associated with changes such as an increase in alcohol and sugar intake while at the same time a decrease in the consumption of fruits and vegetables [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%